Raw Material Procurement Management at SMEs Processing Cashew Nuts (Case Study of CV Hukasari Semesta, Muna Regency, Indonesia) - La Sinaini (Journal of International Conference Proceedings, 2022)
Raw material procurement management is one of the most important activities in production activities. CV Hukasari Semesta is one of the types of micro, small and medium enterprises (SMEs) that is quite developed in Muna Regency which prepares cashew nut products in the form of logs and ready-to-serve. The purpose of this study is to determine the management of raw material procurement by CV Hukasari Semesta in the cashew nut processing business in Mabodo Village, Muna Regency. This research uses descriptive qualitative analysis. The results showed that the management of raw material procurement carried out by CV Hukasari Semesta in ensuring the availability of production raw materials, namely implementing the planning function of raw material procurement, raw material purchasing function, raw material transportation function, raw material sorting function, raw material quality control function, and raw material warehousing function. The implication of this research is that micro, small and medium enterprises (SMEs) in carrying out important business activities apply raw material procurement management to maintain the availability of raw materials during the production process and the quality of the products to be produced.Keywords: management, product, quality, raw material, and SMEs